Place Identity Of The Traditional Courtyard “Late Straits” Eclectic Style Shophouses, George Town Heritage City, Penang - Zwain, Akram M Ali Mahdi (2021)
The traditional shophouses in George Town Heritage City, Malaysia, has special characteristics. These features represent the nature of the place and cultural identity of the people. Over the years, the traditional shophouses courtyard modifications, alterations, and deterioration have become a source of concern to the major stakeholders. Studies have shown that the worst hit among the various shophouses is the traditional courtyard “Late Straits” eclectic style. This study aimed at investigating the place identity which refers to architectural, cultural, and environmental aspects of the traditional courtyard shophouses in George Town, Malaysia. Also, the study proposed a checklist of courtyard architectural characteristics for sustainability and documentation that would reflect the place identity of the Straits Chinese.